2021
DOI: 10.2967/jnumed.121.262296
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of 18F-FDG PET/CT Findings in Patients After COVID-19: An Initial Investigation

Abstract: BackgroundThe aim of this study was to assess the temporal-evolution of pulmonary 18 F-FDG-uptake in patients with Coronavirus Disease (COVID-19) and in Post-COVID-19 Lung-Disease (PCLD). MethodsUsing our hospital's clinical electronic records we retrospectively identified 23 Acute COVID-19, 18 PCLD and 9 completely recovered 18 F-FDG-PET/CT studies during the two peaks of UK pandemic.Pulmonary 18 F-FDG-uptake was measured as a Target-to-Background Ratio (TBRlung=SUVmax/SUVmin) and compared to temporal stage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…Previous work has used FDG-PET as a biomarker for personalized guidance of treatment and prognostication in IPF. More recently the use of FDG-PET in other diffuse lung diseases is becoming recognized e.g., in post COVID lung disease [10]. In addition, understanding the basis of the PET signal may offer us mechanistic insights and identify pharmacological targets regarding brosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has used FDG-PET as a biomarker for personalized guidance of treatment and prognostication in IPF. More recently the use of FDG-PET in other diffuse lung diseases is becoming recognized e.g., in post COVID lung disease [10]. In addition, understanding the basis of the PET signal may offer us mechanistic insights and identify pharmacological targets regarding brosis.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, persistantly high FDG uptake has been reported in a subset of COVID-19 patients with delayed recovery. 15 Thornton et al demonstrated persistent increased pulmonary FDG uptake in patients with post-COVID-19 lung disease (PCLD), and higher in untreated patients compared to those who received high-dose steroids and those who were asymptomatic. The authors concluded that FDG PET/CT may play a role in understanding COVID-19 disease trajectory and guide management for those patients with persistent respiratory symptoms.…”
Section: Molecular Imaging In Covid-19 Detection and Complicationsmentioning
confidence: 99%
“…The authors concluded that FDG PET/CT may play a role in understanding COVID-19 disease trajectory and guide management for those patients with persistent respiratory symptoms. 15 …”
Section: Molecular Imaging In Covid-19 Detection and Complicationsmentioning
confidence: 99%
“…However, an FDG PET/CT study revealed that significant inflammation remained in the lungs, mediastinal LNs, spleen, and liver after two consecutive negative RT-PCR tests in patients recovering from severe COVID-19 infection (47,48). The dissociation between recovery according to CT and delayed recovery of FDG uptake in COVID-19 lesions indicated that a high level of inflammatory change persisted even in the recovery stage with an activated host immune response and/or angiovascular damage (46,(48)(49)(50). 18 F-fluorodeoxyglucose uptake in lymph nodes of patients with COVID-19 18 F-fluorodeoxyglucose uptake in normal-sized LNs is a common observation in patients with COVID-19 and is thought to indicate immunoreactions activated by inflammatory cells such as neutrophils, monocytes, and effector T cells by the release of local chemokines.…”
Section: Covid-19 Pneumoniamentioning
confidence: 99%